ISLAMISASI SAINS DAN KAMPUS PERSPEKTIF A.M. SAEFUDDIN: STUDI DESKRIPTIF ANALISIS - Amir Sahidin (DAS Institute, 2022)
A.M. Saefuddin is one of the thinkers from Indonesia who quickly and swiftly responded to the idea of ​​islamization of knowledge, he called it the term islamization of science and campus. So that in 1983, as Chancellor he declared Ibn Khaldun University (UIKA) as a campus that implemented the Islamization of Science and Campus (ISK). However, a study of the thoughts of A.M. Saefuddin related to ISK is rarely found in various journal articles. For this reason, this article will examine the idea of ​​Islamization of science and campus from the perspective of A.M. Saefuddin. Based on library research with a descriptive analysis approach, it can be concluded, first, the idea of ​​A.M. Saefuddin’s ISK was motivated by the dominance of secular Western science. Secondly, the concept of ISK which was initiated includes the steps of Islamization and the paradigm of unity in tawhid. Third, the implementation of ISK on campus is manifested by what he calls a blue campus, which is a campus that integrates science and technology as its application with religious values. Fourth, although A.M. Saefuddin seems to want to integrate the concept of islamization of knowledge al-Attas and al-Faruqi, but ISK is still relatively abstract and less systematic, because many things have not been explained in more depth and detail.